2003
DOI: 10.1179/cmq.2003.42.2.175
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Approach to Determining the Surface Tension of a Fluid

Abstract: A new formulation has been developed that predicts flow rate of a stream draining from an orifice under the influence of gravity. This model is different from conventional formulations in that it includes the surface tension of the liquid. Results with water and ethylene glycol at various temperatures indicate that it is necessary to account for surface tension under certain conditions including small orifice diameters and operation under low head values. This model is most relevant for liquids of high surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Errors in head, flow rate, and discharge coefficient will contribute to error in calculating these physical properties. Propagation of errors was used to quantify these effects [10] and has been discussed in detail elsewhere [1,2]. It was shown that the propagation of error due to measurements of the flow rate, the discharge coefficient, and head are not significant and will not lead to systematic errors in the values of the physical properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Errors in head, flow rate, and discharge coefficient will contribute to error in calculating these physical properties. Propagation of errors was used to quantify these effects [10] and has been discussed in detail elsewhere [1,2]. It was shown that the propagation of error due to measurements of the flow rate, the discharge coefficient, and head are not significant and will not lead to systematic errors in the values of the physical properties.…”
Section: Resultsmentioning
confidence: 99%
“…As magnesium and its alloys are highly reactive metals, such data are scarce in the literature. This article will report on results on the measurement of the surface tension, viscosity, and density for an AZ91D magnesium alloy under argon and SF 6 using the draining crucible (DC) method [1][2][3]. With this method all three properties are simultaneously calculated from one experimental result for each temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation